EXPLORING THE ROLE OF LANGUAGE ATTITUDES IN SHAPING CLASSROOM INTERACTION IN MALAYSIAN ESL CONTEXTS - Ahmad Sani, Fatin Rahaina; Adilah, Siti Mukhlisa Mohamad Khairul; Jahaya, Nadira M. (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the critical role of language attitudes in shaping classroom interaction within Malaysian ESL contexts, addressing a significant gap in both academic scholarship and educational practice. The problem arises from the limited understanding of how language attitudes - evaluative beliefs and feelings toward specific languages - influence micro-level classroom dynamics, particularly in monolingual settings where English operates alongside Bahasa Malaysia as a national identity marker. While existing literature highlights the impact of macro-level sociolinguistic factors, such as national language policies and societal attitudes, it often neglects the nuanced ways in which attitudes manifest during real-time classroom discourse. This oversight is particularly problematic in Malaysia, where the tension between preserving cultural heritage and embracing global aspirations creates a complex linguistic ecology. The aim of this conceptual paper is to advance theoretical understanding of how language attitudes mediate classroom interactions and influence learning outcomes and social cohesion. Through a synthesis of relevant literature, the study identifies gaps in qualitative research on micro-level processes, cross-disciplinary perspectives, and context-specific frameworks tailored to monolingual ESL settings. A proposed conceptual framework integrates micro-level interactional dynamics with broader sociocultural influences, offering practical insights for educators and policymakers. The main findings reveal that positive language attitudes toward English foster inclusivity and collaboration, while negative attitudes hinder student engagement and communicative competence. Furthermore, the study underscores the need for evidence-based pedagogical strategies and longitudinal research to track the evolution of language attitudes over time. The implications extend beyond academia, informing policy development and professional practices that align with Malaysia’s sociocultural realities and global aspirations. By bridging theory and practice, this study contributes to creating inclusive, effective, and forward-looking ESL classrooms, ultimately enhancing both language learning outcomes and social cohesion in Malaysia’s increasingly globalised society.